2022
DOI: 10.3389/fenvs.2022.862310
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Ecosystems and Socioeconomic Systems to Identify Ecological Security Pattern and Restoration Strategy in a Rapidly Urbanizing Landscape

Abstract: The rapid process of urbanization has been accompanied by a disordered expansion of construction land, which has resulted in the degradation of ecosystem services. The identification of ecological security patterns (ESPs) is an important means to coordinating human-land relationships and carrying out ecological restoration strategies, which are of great significance to protecting ecological sustainability. However, previous studies have ignored the mutual impact of urbanization and ecological protection, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Numerous studies have demonstrated that one of the key contributing factors to the decline in ecosystem services was the process of rapid urbanization, which was accompanied by the sprawl of construction land (Tan et al, 2022;Tiando et al, 2021). Despite having a high construction intensity in this study, Huaxi District had the highest supply and the largest area of carbon sequestration due to its abundance of natural green space.…”
Section: Carbon Sequestration Service Flowmentioning
confidence: 76%
“…Numerous studies have demonstrated that one of the key contributing factors to the decline in ecosystem services was the process of rapid urbanization, which was accompanied by the sprawl of construction land (Tan et al, 2022;Tiando et al, 2021). Despite having a high construction intensity in this study, Huaxi District had the highest supply and the largest area of carbon sequestration due to its abundance of natural green space.…”
Section: Carbon Sequestration Service Flowmentioning
confidence: 76%
“…The ACO-based GeoSOS area optimization model ) has been widely applied in land use optimization and nature reserve siting studies (Mi et al 2015Liu et al 2011, which can identify ecological sources with a more compact pattern (Liu et al 2012). In addition, the current ES-based ecological source identification ignores the differences in the importance of various ES during the regional development process (Tan, Li and Lin 2022Dai, Liu and Luo 2021Lin et al 2017. Simply assigning the same weights to ESs may lead to biased results (Ramel et al 2020), missing high-functioning ecological sources or identifying unnecessary areas.…”
Section: Introductionmentioning
confidence: 99%